PENGARUH TERAPI MUSIK KLASIK TERHADAP KECEMASAN PASIEN PRE OPERASI DI INSTALASI BEDAH PUSAT RSUP H. ADAM MALIK MEDAN TAHUN 2018 - Basri, Basri (Jurnal Keperawatan Priority, 2019)
Anxiety that is not handled properly can cause physical and psychological changes that ultimately can improve sympathetic nervous work and will increase heart rate, breath frequency, blood pressure, cold sweats, heartburn, urinary disorders, and generally reduce the energy level on patients thus harming the patient itself. In preoperative times patients face various stressors that cause anxiety. The development of music has a therapeutic effect in overcoming mood disorders, such as anxiety. This study aims at the influence of classical music therapy on preoperative patient anxiety at the Central Surgery Installation RSUP H. Adam Malik Medan. The type of research used in this research is quasi-experiment method through one group pretest post test design approach with 32 pre-operation respondents aged over 18 years. Data were collected using questionnaires. The result of bivariate analysis of this study is the influence of music therapy on preoperative anxiety in the Central Surgery Installation of RSUP. H. Adam Malik Medan shows p value = 0.000, and 0.000 <0,05 which means there is significant influence from giving classical music therapy on T test that is before given music therapy got result of test of T 382.531 become 301.288 (81,243). The results of this study It is expected to be a consideration of hospitals or nurses to make music therapy as one of nursing intervention in helping alleviate anxiety in preoperative patients who experience anxiety.